ASESMEN DIAGNOSTIK MAKRO PERSIAPAN PENERAPAN KURIKULUM MERDEKA MTsN 28 JAKARTA - Asip Suryadi; Siti Husna (JENTRE, 2022)
This study examines the diagnostic assessment results of reading, writing and mathematics prerequisite skills of 192 grade VII MTsN 28 Jakarta students. The assessment measures reading and writing in Arabic and Latin, and application level of mathematics for the needs of implementing the Kurikulum Merdeka. The assessment was carried out on the 11th of July 2022 using online questions and written tests in reading, writing and mathematics in the level of elementary school curriculum. The results of the assessment are processed with descriptive statistics and interpreted into certain qualitative level of competencies. In addition, the results are interpreted form the perspective of AKM (minimum competency assessment), the Indonesia national assessment system. The results shows that 7% of students are not fluent in reading Arabic, 17% are not fluent in writing Arabic, 44% had low level in reading comprehension, and 10% Latin writing of the students are still difficult to read. Likewise in basic mathematics application, 42% of students are still in low level. In terms of AKM perspective as a whole, the literacy and numeracy levels have not yet reached the minimum competence. The results of the assessment have two implications. Firstly, the madrasah should organize a preliminary learning to help the students master prerequisite skills. Secondly in terms of AKM, madrasah should carry out curriculum engineering to improve the quality of literacy and numeracy-based learning.